2017
DOI: 10.1073/pnas.1616060114
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 haploinsufficiency suppresses acinar-to-ductal metaplasia, signaling, and mutant Kras -driven pancreatic tumorigenesis in mice

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a highly lethal disease in critical need of new therapeutic strategies. Here, we report that the stress-inducible 78-kDa glucose-regulated protein (GRP78/HSPA5), a key regulator of endoplasmic reticulum homeostasis and PI3K/AKT signaling, is overexpressed in the acini and PDAC of Pdx1-Cre;Kras G12D/+ ;p53 f/+ (PKC) mice as early as 2 mo, suggesting that GRP78 could exert a protective effect on acinar cells under stress, as during PDAC development. The PKC pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…Furthermore, targeted heterozygous knockout of Grp78 in bone marrow suppressed blast numbers without affecting normal hematopoiesis (46). Recently, using the Pdx1 Cre -Ras G12D/þ -P53 fl/þ model for pancreatic ductal carcinoma, it was shown that epithelium-specific heterozygosity of Grp78 resulted in reduced tumorigenesis and increased survival of mice (47). Pancreatic ductal cells are known for their large translational capacity and dependence on the ER and thus on Grp78 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, targeted heterozygous knockout of Grp78 in bone marrow suppressed blast numbers without affecting normal hematopoiesis (46). Recently, using the Pdx1 Cre -Ras G12D/þ -P53 fl/þ model for pancreatic ductal carcinoma, it was shown that epithelium-specific heterozygosity of Grp78 resulted in reduced tumorigenesis and increased survival of mice (47). Pancreatic ductal cells are known for their large translational capacity and dependence on the ER and thus on Grp78 levels.…”
Section: Discussionmentioning
confidence: 99%
“…PKC mice showed detectable PDAC by 3 months and rapid subsequent tumor growth, associating with upregulation of Grp78 and the phosphorylated form of eukaryotic translation initiation factor 2 a (eIF2a) in the ductal cells, indicative of ER stress. 5 While homozygous knockout of Grp78 in the pancreas led to extensive fat infiltration and poorly developed acinar cells, heterozygous Grp78 knockout with 50% reduction in Grp78 level had no effect on pancreas development and function; thus, it is well suited for studying the role of Grp78 in PDAC and it also more closely mimics what can be achieved in the clinic with therapeutic agents.…”
Section: Role Of Grp78 In Pdac and Admmentioning
confidence: 99%
“…Through creation of the PKC78 C/¡ (Pdx-Cre;Kras G12D/C ; p53 C/¡ ;Grp78 C/¡ ) model, we established that Grp78 haploinsufficiency in the pancreas is sufficient to reduce proliferation, suppress activation of Akt, ribosomal protein S6 (S6), extracellular regulated MAP kinase (Erk), and signal transducer and activator of transcription 3 (Stat3), delay tumor growth and significantly prolong survival. 5 Previous studies have shown that acinar cells expressing mutant Kras G12D are induced to transdifferentiate through the process of ADM recently recognized as a key tumor initiation event of PDAC. 1 Importantly, we discovered that PKC78 C/¡ pancreata exhibited reduced ADM, as well as deficient ADM in acinar cells isolated from the heterozygous Grp78 pancreas in response to transforming growth factor a (TGFa) stimulation.…”
Section: Role Of Grp78 In Pdac and Admmentioning
confidence: 99%
See 1 more Smart Citation
“…To survive the pressure created by the tumor microenvironment, including hypoxia and nutrient deprivation, tumor cells utilize the UPR pathways (Avril et al ., 2017; Chevet et al ., 2015; Lee, 2007; Ma and Hendershot, 2004). Multiple components of the UPR have been linked to advanced tumor stage and chemoresistance in cancer (Lee, 2014; Roller and Maddalo, 2013; Shen et al ., 2017; Wang and Kaufman, 2014). For example, overexpression of PDIA5 in chronic myeloid leukemia shows increased resistance to imatinib (Chevet et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%